2020
DOI: 10.3390/ijms21082875
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Na,K-ATPase as a Target for Circulating Ouabain

Abstract: While the role of circulating ouabain-like compounds in the cardiovascular and central nervous systems, kidney and other tissues in health and disease is well documented, little is known about its effects in skeletal muscle. In this study, rats were intraperitoneally injected with ouabain (0.1–10 µg/kg for 4 days) alone or with subsequent injections of lipopolysaccharide (1 mg/kg). Some rats were also subjected to disuse for 6 h by hindlimb suspension. In the diaphragm muscle, chronic ouabain (1 µg/kg) hyperpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 68 publications
9
13
1
Order By: Relevance
“…However, ouabain can modulate ion transport in rat skeletal muscle by inhibiting the ouabain-sensitive NKAα2 subunit (Chibalin et al, 2012). Further, low concentrations of ouabain (10-20 nM) were shown to affect the skeletal muscle function in rats (Kravtsova et al, 2020). Our results in L6 cells therefore do not exclude the possibility that ouabain modulates IL-6/STAT3 signaling in rat skeletal muscle.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…However, ouabain can modulate ion transport in rat skeletal muscle by inhibiting the ouabain-sensitive NKAα2 subunit (Chibalin et al, 2012). Further, low concentrations of ouabain (10-20 nM) were shown to affect the skeletal muscle function in rats (Kravtsova et al, 2020). Our results in L6 cells therefore do not exclude the possibility that ouabain modulates IL-6/STAT3 signaling in rat skeletal muscle.…”
Section: Discussioncontrasting
confidence: 59%
“…In cultured skeletal muscle cells and isolated skeletal muscle, ouabain stimulates the glycogen synthesis ( Clausen, 1965 ; Kotova et al, 2006a , b ), suggesting a role for CTS and NKA in regulation of skeletal muscle metabolism ( Pirkmajer and Chibalin, 2016 ). Interestingly, recent data suggest that circulating ouabain may regulate NKA in skeletal muscle and oppose depolarization of the sarcolemma due to muscle disuse or exposure to lipopolysaccharide ( Kravtsova et al, 2020 ). Clearly, the role of CTS in skeletal muscle needs to be dissected in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…In the control, at 30 min of registration, TER values of the jejunum and the colon were 50 ± 4 Ohm·cm 2 ( n = 23) and 57 ± 4 Ohm·cm 2 ( n = 30), respectively, and remained stable during 60 min of the experiment ( Figure 2 a,b). Chronic administration of ouabain (1 µg/kg) significantly ( p < 0.05) increased the level of circulating ouabain in rat serum from 2.6 ± 0.3 nM in control up to 4.7 ± 1.5 nM (see also [ 33 ]). Ouabain treatment did not significantly affect TER of both jejunum and colon ( Figure 2 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged exposure to microgravity [ 37 ] or HS (a well-accepted animal ground-based spaceflight model) [ 38 , 39 ] are known to impair intestinal function that reduces its resistance to bacterial infection [ 39 ]. It was recently shown that the first 6 h of HS disturbs rat postural soleus muscle function and depolarizes the muscle membrane, while pre-treatment with ouabain (1 µg/kg) protects against this disturbance [ 33 ]. The effect of an acute HS on the gut function was not assessed yet.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one of the reasons for the sub-threshold depolarization of the membrane at the initial stage of unloading may be AMPK dephosphorylation. Another possible cause for the decrease in RMP may be a change in the concentration of circulating ouabain [ 81 ]. In addition, the decrease in RMP in rat soleus during the first hours of unloading is accompanied by a disruption of lipid rafts in sarcolemma [ 82 , 83 ].…”
Section: E3-ubiquitin Ligase Expression Control Irs-1 Degradationmentioning
confidence: 99%